AB0158 The z-score for the quantification of joint space narrowing in rheumatoid arthritis – a subanalysis of the lemeradix register -. (23rd January 2014) - Pfeil, A.; Böttcher, J.; Bornholdt, K.; Oelzner, P.; Wolf, G.
Abstract : Background: The reduction of finger joint space width in patients with rheumatoid arthritis (RA) is associated with joint damage and physical function loss of the finger joints which results in physical disability. Objectives: The Z-Score is a new computer based technique to measure joint space reduction on hand radiographs in RA in a gender- and age-independent way. The aim of this study was to quantify longitudinal changes of joint space width by the Z-Score in comparison to the Sharp joint space narrowing score. Methods: 94 RA-patients (68 women and 26 men) participating at the LEMERADIX REGISTER (Retrospective Comparison of Leflunomide and Methotrexate in Rheumatoid Arthritis by Digital Radiogrammetry (DXR) and Computer-aided Joint Space Analysis (CAJSA)) as a prospectively planned, comparative, multicenter retrospective study were included. 53 patients were treated with 15 mg methotrexate per week and 41 patients were treated with 10 mg leflunomide per day over an observation period of 1.8 years. Hand radiographs were acquired at baseline and after 1.8 years. The quantification of finger joint space width of the metacarpal-phalangeal articulations (MCP) was performed by the Z-score using the computer-assisted joint space analysis (Version 1.3.6; Sectra; Sweden) and the Sharp joint space narrowing score. Results: For both treatment arms (leflunomide and methotrexate) no significant changes of the Sharp Erosion Score and Sharp joint space narrowing score were observed over the observation period of 1.8 years. The median Sharp joint space narrowing score of the first and second measurement was 1. For the methotrexate treated patients the Z-Score (MCP total) decreased (-0.13 SD) from 0.08 SD (initial measurement) to -0.05 SD (second measurement). Regarding, the leflunomide-group the Z-Score (MCP total) was not significantly reduced (-0.03 SD) from 0.16 SD (initial measurement) to 0.13 SD (second measurement). Conclusions: In this longitudinal head to head comparison based on the LEMERADIX-Register the conventional scoring of the finger joint space width by the Sharp joint space narrowing score revealed no change of the median joint space width. The automatically quantification of the joint space width using the Z-Score was able to detect changes of finger joint space width in patient groups with different treatment arms. Consequently, the automatic quantification of finger joint space width by the Z-Score is a sensitive technique for the quantification of joint space reduction and treatment effects. Disclosure of Interest: A. Pfeil Speakers bureau: speaker's fees from sanofi-aventis, J. Böttcher Speakers bureau: speaker's fees from sanofi-aventis, K. Bornholdt Employee of: full-time employee of Sanofi-Aventis Deutschland GmbH, Germany, P. Oelzner: None Declared, G. Wolf: None Declared